Visceral leishmaniasis in acute myeloid leukemia revealed on peripheral blood smear. Issue 8 (4th June 2018) - Moniot, Maxime; Loyens, Maxime; Mary, Charles; L'Ollivier, Coralie
Key Clinical Message: Images of parasitic forms of Leishmania infantum are typical in the hands of a skilled expert but should be known by biologists of Hematology Department. In an endemic region, the diagnosis of visceral leishmaniasis (VL) must be considered because of its potential role in accelerating hematological malignancy. Abstract : Images of parasitic forms of Leishmania infantum are typical in the hands of a skilled expert but should be known by biologists of Hematology Department. In an endemic region, the diagnosis of visceral leishmaniasis (VL) must be considered because of its potential role in accelerating hematological malignancy.